First, we will use the first equation y = 2 + 3x to substitute for y in the second equation:
4x - 3(2 + 3x) = -16
4x - 6 - 9x = -16
-5x - 6 = -16
-5x = -10
x = 2
Now that we have found the value of x, we can substitute it back into the first equation to find the value of y:
y = 2 + 3(2)
y = 2 + 6
y = 8
Therefore, the solution to the system of equations is x = 2 and y = 8.
Solving Equations Using Substitution Quick Check
Solve the system of two equations using substitution y = 2 + 3x; 4x - 3y = - 16 (1 point )
1 answer